2023
DOI: 10.1021/acs.biochem.3c00012
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 3,6-Dideoxy-heptoses for the Capsular Polysaccharides of Campylobacter jejuni

Abstract: Campylobacter jejuni is the leading cause of food poisoning in the United States. Surrounding the exterior surface of this bacterium is a capsular polysaccharide (CPS) that helps protect the organism from the host immune system. The CPS is composed of a repeating sequence of common and unusual sugar residues, including relatively rare heptoses. In the HS:5 serotype, we identified four enzymes required for the biosynthesis of GDP-3,6-dideoxy-β-l-ribo-heptose. In the first step, GDP-d-glycero-α-d-manno-heptose i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(35 citation statements)
references
References 25 publications
0
35
0
Order By: Relevance
“…In serotypes HS:5 and HS:11, the C5-epimerase inverts the stereochemistry at C5 to form GDP-3,6-dideoxy-4-keto-β- l - xylo -heptose ( 17 ). We have previously shown that the C4-reductases from HS:3 and HS:53 can reduce the 4-keto group of 16 to form the previously unknown compounds, GDP-3,6-dideoxy-α- d - arabino -heptose ( 20 ) and GDP-3,6-dideoxy-α- d - lyxo -heptose ( 21 ), respectively . These results demonstrate that the C4-reductases that appear in gene clusters for the biosynthesis of GDP-6-deoxy-heptoses can also function with GDP-4-keto-3,6-dideoxy substrates to generate 3,6-dideoxy heptoses that have not previously been identified within the CPS structures of C. jejuni .…”
Section: Resultsmentioning
confidence: 69%
See 4 more Smart Citations
“…In serotypes HS:5 and HS:11, the C5-epimerase inverts the stereochemistry at C5 to form GDP-3,6-dideoxy-4-keto-β- l - xylo -heptose ( 17 ). We have previously shown that the C4-reductases from HS:3 and HS:53 can reduce the 4-keto group of 16 to form the previously unknown compounds, GDP-3,6-dideoxy-α- d - arabino -heptose ( 20 ) and GDP-3,6-dideoxy-α- d - lyxo -heptose ( 21 ), respectively . These results demonstrate that the C4-reductases that appear in gene clusters for the biosynthesis of GDP-6-deoxy-heptoses can also function with GDP-4-keto-3,6-dideoxy substrates to generate 3,6-dideoxy heptoses that have not previously been identified within the CPS structures of C. jejuni .…”
Section: Resultsmentioning
confidence: 69%
“…The C4-keto functional group in GDP-6-deoxy-4-keto-α- d - lyxo -heptose ( 5 ) renders the stereochemical configuration at C3 and C5 susceptible to racemization via an enolate intermediate that is formed by proton abstraction from either C3 and/or C5. , Within the 33 common serotypes of C. jejuni , there are three types of C3- and C5-epimerases that have been identified thus far. ,,, The sequence similarity network (SSN) for the epimerases found within the gene clusters for heptose biosynthesis in C. jejuni is presented in Figure at a sequence identity cutoff of 89%. , The C3-epimerases have been shown to catalyze the epimerization of 6 to form GDP-6-deoxy-4-keto-α- d - arabino -heptose ( 7 ), whereas the C3/C5-epimerases have been shown to catalyze the epimerization of both C3 and C5 to generate an equilibrium mixture with GDP-6-deoxy-4-keto-β- l - ribo -heptose ( 8 ) and GDP-6-deoxy-4-keto-β- l - xylo -heptose ( 9 ), in addition to 7 . , Ten serotypes (HS:3, HS:4, HS:8, HS:10, HS:12, HS:23/36, HS:29, HS:33, HS:41, and HS:52) contain a C3-epimerase (91–99% identical to one another), whereas five of the serotypes (HS:2, HS:15, HS:32/HS:58, HS:42, and HS:63) have the gene for the C3/C5-epimerase (81–98% identical to one another). Five serotypes (HS:18, HS:27, HS:40, HS:51/HS:53, and HS:60) do not contain either a C3 or C3/C5-epimerase and are thus highly likely to utilize either GDP- d - glycero - d - manno -heptose ( 5 ) or GDP-6-deoxy- d - manno -heptose ( 10 ) in their ultimate capsular polysaccharide.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations